Religion and the body modern science and the construction of religious meaning - Cave, David; Norris, Rebecca Sachs (Leiden Boston Brill, 2012)
This book reflects on the implications of neurobiology and the scientific worldview on aspects of religious experience, belief, and practice. Just as interest in the neurosciences and related fields has burgeoned in contemporary society, interest in the fields of neuroscience and cognitive studies is also growing within the religious studies academy, and reflection on these shifts is well overdue. How do religious practitioners negotiate the interconnection of science and religion? What can the neurosciences add to scholars' understanding of religion and to how humans construct religious meaning?
Includes bibliographical references and index
Keywords: Neurosciences -- Religious aspects; Neurobiology; Religion and science; Religion; Electronic books; Aufsatzsammlung